Sad Kertih: Realizing Holistic and Sustainable Development through Balinese Socio-cultural Capital - Ida Bagus Gde Yudha Triguna; Anak Agung Inten Mayuni; Nanang Sutrisno (International Journal of Religious and Cultural Studies, 2022)
The success of a country's development and progress is almost entirely measured according to the categories constructed by the West. The stratification of developed and developing countries has become a discourse that strengthens the hegemony of the West over non-Western countries. This classification has ignored the cultural reality that every nation has its view of the success of development by the goals and ideals of its own life. For Eastern people, material progress is not the only measure for the success of development because they have a more essential orientation, namely the happiness of the soul. Balinese people also believe that the purpose of human life is to achieve material well-being (jagadhita) as well as spiritual happiness (moksa) integrally. This means that development must be carried out holistically to realize these goals. Through a literature review of the Purana Bali, six important concepts for holistic and sustainable development of Bali were found, namely Sad Kertih which includes Atma Kertih, Jana Kertih, Jagat Kertih, Danu Kertih, Samudra Kertih, and Wana Kertih. These six concepts are correlated with the Tri Hita Karana (three causes of happiness) including parhyangan, pawongan, and palemahan. Sad Kertih became one of the sociocultural and local geniuses of the Balinese people to face Western hegemony in development, as well as to realize the harmony of civilization.